Mathematical modelling of tuberculosis transmission and impact of Isoniazid Preventive Therapy in Malaysia / Nurhuda Ismail - Nurhuda, Ismail (2017)
Tuberculosis remains one of the highest unresolved disease burden among re-emerging diseases in Malaysia for the last thirty years. The current treatment protocol guideline emphasizes treatment for only infectious tuberculosis patients. This study aimed to investigate tuberculosis transmission dynamics exclusive to the Malaysian environment and characteristics. This study applied the infectious disease modelling techniques to study the progression of latent tuberculosis infection and assess the likely impact of Isoniazid Preventive Therapy for latent tuberculosis high risk subpopulations in reducing tuberculosis incidence in Malaysia. Methods: This study explored the epidemiology of tuberculosis in Malaysia to develop a deterministic compartmental age-structured tuberculosis model which incorporated treatment for infectious as well as early preventive therapy for latent. The model assumed latently infected individuals develop infectious state of tuberculosis as a result of primary infection, endogenous reactivation and exogenous reinfection. This study assessed the likely impact of interventions in Malaysia by formulating and analysing the model under various scenarios. These included no intervention strategy then, extended to incorporate the Isoniazid Preventive Therapy only, treatment of infectious tuberculosis only and combination treatment of infectious tuberculosis and Isoniazid Preventive Therapy. The equilibrium of the model was determined, and stabilities were analysed. The model fitting and validation were performed. The national tuberculosis incidence was estimated and projected from 1990 till 2050. The effective reproduction numbers for the model were compared to assess the possible population benefits achieved by no intervention, treatment of infectious tuberculosis only, Isoniazid Preventive Therapy only and a combination treatment of infectious tuberculosis and Isoniazid Preventive Therapy for the latents. The model further determined the effectiveness of Isoniazid Preventive Therapy for early latent tuberculosis infection and quantified coverage of the iv strategy to eliminate tuberculosis, when used in conjunction with treatment of infectious tuberculosis. The model then compared the selection of early latent tuberculosis infection versus late latent tuberculosis infection to effectively reduce the incidence of tuberculosis in Malaysia. Results: A transmission dynamic mathematical model of tuberculosis exclusive to Malaysian environment and characteristics was developed. The model projected a higher and increasing trend of national tuberculosis incidence till year 2030 at annual increment rates from 1% to 5.5%. Application of this model showed that combination treatment strategy of Isoniazid Preventive Therapy for early high risk latent tuberculosis sub-populations with current treatment for infectious tuberculosis is the most effective strategy for controlling tuberculosis epidemic in Malaysia. However, a minimal ten percent coverage of Isoniazid Preventive Therapy in population is required for effective reduction following eight to ten years of successful implementation with expected cumulative incidence reduction of 27.21% by 2050. Conclusion: Isoniazid Preventive Therapy may have substantial effect on controlling tuberculosis epidemic in Malaysia when used in conjunction with current treatment regime for infectious tuberculosis. However, a minimal ten percent coverage among the early latent tuberculosis infection sub-populations must be ensured to achieve effective reduction in incidence. This can be achieved by expansion of coverage to other high risk latent tuberculosis sub-populations such as healthcare workers, close contacts and in institutionalized settings, with comprehensive protocol and surveillance